Current condition of lignite mining in Oltenia coal basin and solutions for reuse of mined-out space of closed pits - Izabela-Maria Nyari (Apostu) (Горные науки и технологии, 2018)
Oltenia Coal Basin occupies the area of 4500 km2 and encloses the most important deposits of lignite in Romania, many of which are exploited by open-pit mining. Open-pit lignite mining involves long-term occupancy of large areas and considerable negative impact on physical, chemical and structural characteristics of the lands that define the regional terrain, resulting in full degradation of previously existed landscape. The degraded lands require great efforts on their reclamation for recultivation of soils, recovering landscape and overall mitigation of mining environmental impact. Selecting post-mining use of remaining mined-out pit space is performed taking into account such criteria as climate, geomorphology, pit slope stability conditions, regional development strategy, local community requirements, financial resources, etc.